Development of Locomotor-Related Movements in Early Infancy - Dewolf, Arthur H.; Sylos Labini, Francesca; Ivanenko, Yury; Lacquaniti, Francesco (Frontiers in Cellular Neuroscience, 2021)
This mini-review focuses on the emergence of locomotor-related movements in early infancy. In particular, we consider multiples precursor behaviours of locomotion as manifestation of the development of the neuronal networks and their link in the establishment of precocious locomotor skill. In spite of the large variability of motor behaviour observed in human babies, as in animals, afferent information is already processed to shape the behaviour to specific situations and environments. Specifically, we argue that the closed-loop interaction between the neural output and the physical dynamics of the mechanical system should be considered to explore the complexity and flexibility of pattern generation in human and animal neonates.